(untitled) (World Bulletin of Social Sciences, 2024)
In this article, the scientific views on the formation of elements of a scientific worldview in primary-grade native language classes and the development of the information resources integration system in this process are presented. This scientific work is intended for university students, masters, doctoral students, researchers and a wide audience.